Label free redox capacitive biosensing - Fernandes, Flávio C. Bedatty [UNESP]; Góes, Márcio S. [UNESP]; Davis, Jason J.; Bueno, Paulo Roberto [UNESP] (Elsevier, 2013)
A surface confined redox group contributes to an interfacial charging (quantifiable by redox capacitance) that can be sensitively probed by impedance derived capacitance spectroscopy. In generating mixed molecular films comprising such redox groups, together with specific recognition elements (here antibodies), this charging signal is able to sensitively transduce the recognition and binding of specific analytes. This novel transduction method, exemplified here with C-reactive protein, an important biomarker of cardiac status and general trauma, is equally applicable to any suitably prepared interfacial combination of redox reporter and receptor. The assays are label free, ultrasensitive, highly specific and accompanied by a good linear range. © 2013 Elsevier B.V.
Keywords: Biosensor; Capacitance spectroscopy; Immunosensors; Redox capacitance; C-reactive proteins; Interfacial charging; Molecular films; Specific recognition; Transduction method; Ultra sensitives; Biosensors; Capacitance; antibody; C reactive protein; binding affinity; biosensor; capacitance spectroscopy; controlled study; electric capacitance; electrode; immunosensor; molecular recognition; oxidation reduction state; reproducibility; sensitivity and specificity; spectroscopy